Approaches to the Training of Engineering Personnel in the Context of Digital Transformation of Education - I. V. Shatskaya (Цифровая трансформация, 2024)
The relevance of the article is due to the increased importance of training engineering personnel in the context of the global digital transformation of the economy and social sphere, as well as the rapid acceleration of the pace of technological development. In order to avoid Russia's technological lag behind leading countries in the field of implementation and use of digital technologies in a variety of fields of activity, attention should be paid to the organization and content of higher technical education. The author considers it necessary to use competency-based and interdisciplinary approaches as basic ones when teaching the disciplines of the humanities and socio-economic blocks for future engineers. As part of the competency-based approach in the context of the digital transformation of education, it is proposed to actively use the gamification method in the educational process due to its obvious advantages: increasing the involvement of students in the educational process, increasing the motivation of students, etc. To substantiate the findings, a set of scientific methods and approaches was used: analysis and synthesis, comparisons, generalizations, scientific abstractions.